European reference values for the quality of life questionnaire EORTC QLQ-C30: Results of a German investigation and a summarizing analysis of six European general population normative studies. (July 2014) - Hinz, Andreas; Singer, Susanne; Brähler, Elmar
Abstract Background. The aims of this study are to present the results of a new general population normative study of the quality of life questionnaire EORTC QLQ-C30 and to give European reference values averaged across six studies. Methods. The empirical study was based on a representative sample of the German adult population (N = 2448). The subjects were asked to fill in several questionnaires, one of them being the EORTC QLQ-C30. Results. EORTC QLQ-C30 mean scores of this sample indicated slightly better quality of life (QoL) than in previous European studies. QoL decreased with age, but there were only small gender differences. The mean scores were compared with the age and gender adjusted scores of five other European normative studies from Sweden, the Netherlands, Norway, and Germany (N between 1731 and 4910). Finally, the data of these five studies and the new study were combined to arrive at averaged European normative values for the scales and the symptom items of the questionnaire. Conclusion. The reference values of the scales pooled across six European studies (N = 16 151) can be used as general population references for QoL scores of cancer patients.